2014
DOI: 10.1262/jrd.2013-116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trichostatin A on <i>In Vitro</i> Development and DNA Methylation Level of the Satellite I Region of Swamp Buffalo (<i>Bubalus bubalis</i>) Cloned Embryos

Abstract: Trichostatin A (TSA), a histone deacetylase inhibitor, has been widely used to improve the cloning efficiency in several species. This brings our attention to investigation of the effects of TSA on developmental potential of swamp buffalo cloned embryos. Swamp buffalo cloned embryos were produced by electrical pulse fusion of male swamp buffalo fibroblasts with swamp buffalo enucleated oocytes. After fusion, reconstructed oocytes were treated with 0, 25 or 50 nM TSA for 10 h. The results showed that there was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
(43 reference statements)
0
4
1
Order By: Relevance
“…In Experiment 1, following treatment of fused embryos with TSA (50 or 75 nM), the cleavage and blastocyst rate, TCN and apoptotic index were not found to be significantly different from those of controls, at both the concentrations examined (Table 1) indicating that neither the in vitro developmental competence nor the embryo quality were improved by TSA treatment. This is contrary to the results of earlier reports in cattle (Enright et al, 2003;Ding et al, 2008) and those of previous study in buffalo (Luo et al, 2013;Srirattana et al, 2014;Saini et al, 2014) in which TSA treatment of donor cells or embryos or both was found to improve the blastocyst rate and/or TCN of blastocysts. As the ability to be reprogrammed varies considerably among different cell types (Oback & Wells 2002), is possible that this disparity in the effects of TSA may be because we have used semen-derived epithelial cells in the present study whereas skin-derived fibroblasts had been used in the earlier studies mentioned above.…”
Section: Resultscontrasting
confidence: 99%
“…In Experiment 1, following treatment of fused embryos with TSA (50 or 75 nM), the cleavage and blastocyst rate, TCN and apoptotic index were not found to be significantly different from those of controls, at both the concentrations examined (Table 1) indicating that neither the in vitro developmental competence nor the embryo quality were improved by TSA treatment. This is contrary to the results of earlier reports in cattle (Enright et al, 2003;Ding et al, 2008) and those of previous study in buffalo (Luo et al, 2013;Srirattana et al, 2014;Saini et al, 2014) in which TSA treatment of donor cells or embryos or both was found to improve the blastocyst rate and/or TCN of blastocysts. As the ability to be reprogrammed varies considerably among different cell types (Oback & Wells 2002), is possible that this disparity in the effects of TSA may be because we have used semen-derived epithelial cells in the present study whereas skin-derived fibroblasts had been used in the earlier studies mentioned above.…”
Section: Resultscontrasting
confidence: 99%
“…Epigenetic modifications such as DNA methylation and histone modifications play an important role in embryonic development (Niemann, 2016 ; Sproul et al, 2005 ). Aberrant epigenetic modifications such as DNA methylation and histone acetylation, and also abnormal gene expression patterns for example insulin‐like growth factors (IGF‐1 and IGF‐2) have been found in cloned buffalo embryos when compared with those of IVF embryos (Jyotsana et al, 2016 ; Luo et al, 2013 ; Mohapatra et al, 2015 ; Pandey et al, 2009 ; Saini et al, 2016 , 2017 ; Srirattana et al, 2014 ; Sun et al, 2015 ; Suteevun, Parnpai, et al, 2006 ; Suteevun, Smith, et al, 2006 ).…”
Section: Scntmentioning
confidence: 99%
“…Significant improvement in mouse cloning was found when TSA was treated on reconstructed oocytes/embryos (Kishigami et al, 2007 ). In SCNT swamp buffalo, treatment of TSA at 25 nM for 10 h on reconstructed oocytes could enhance embryo development, but no beneficial effect on the DNA methylation level was observed (Srirattana et al, 2014 ). When HMC river buffalo embryos treated with 75‐nM TSA for 10 h, the global level of histone H4 lysine 5 acetylation (H4K5ac) in blastocysts was increased and level of histone H3 lysine 27 trimethylation (H3K27me3) were decreased, however, the global level of histone H3 lysine 18 acetylation (H3K18ac) was not affected (Selokar et al, 2015 ).…”
Section: Scntmentioning
confidence: 99%
“…Some reports have demonstrated that scripted treatment after somatic cell nuclear transfer (NT) improves the success rate of bovine embryo cloning ( Ding et al, 2008 and Xu et al, 2013 ). To the best of the author’s knowledge, followed by an assessment of the literature, the reports on the comparison of the two technologies have been rare ( Lee et al, 2016 ; and Srirattana et al, 2014 ). Therefore, this study aims to compare the effect of the TSA and SCR in the development of the SCNT cloned Namey sheep embryos in vitro .…”
Section: Introductionmentioning
confidence: 99%